Influence of emulsion systems of cryoprotective action оn thermophysical properties of meat systems - Янчева, Марина Олександрівна; Дроменко, Елена Борисовна; Потапов, Владимир Алексеевич; Гринченко, Ольга Алексеевна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper gives the results of studying the thermophysical properties of meat systems based on minced beef, pork and adipose tissue during freezing and thawing. It is shown that the morphological structure of meat (the proportion of muscle, connective and adipose tissue) and its chemical composition has a significant influence on the technological parameters of minced meat semi-finished products in implementing the freeze-thaw cycle. A hypothesis on possible use of emulsion systems as the components of cryoprotective action in the technology of frozen minced meat semi-finished products was proved. Based on a comprehensive study of the thermophysical properties of the meat systems (cryoscopic temperature range, specific heat of phase transition and the fraction of moisture, changing the aggregation state, in the cryoscopic temperature range), the rational content of the emulsion system consisting of frozen minced meat semi-finished products was justified.